Repurposing live attenuated trivalent MMR vaccine as cost-effective cancer immunotherapy - Zhang, Yuguo; Gabere, Musa; Taylor, Mika A.; Simoes, Camila C.; Dumbauld, Chelsae; Barro, Oumar; Tesfay, Mulu Z.; Graham, Alicia L.; Ferdous, Khandoker Usran; Savenka, Alena V.; Chamcheu, Jean Christopher; Washam, Charity L.; et al. (Frontiers in Oncology, 2022)
It has long been known that oncolytic viruses wield their therapeutic capability by priming an inflammatory state within the tumor and activating the tumor immune microenvironment, resulting in a multifaceted antitumor immune response. Vaccine-derived viruses, such as measles and mumps, have demonstrated promising potential for treating human cancer in animal models and clinical trials. However, the extensive cost of manufacturing current oncolytic viral products makes them far out of reach for most patients. Here by analyzing the impact of intratumoral (IT) administrations of the trivalent live attenuated measles, mumps, and rubella viruses (MMR) vaccine, we unveil the cellular and molecular basis of MMR-induced anti-cancer activity. Strikingly, we found that IT delivery of low doses of MMR correlates with tumor control and improved survival in murine hepatocellular cancer and colorectal cancer models via increased tumor infiltration of CD8+ granzyme B+ T-cells and decreased macrophages. Moreover, our data indicate that MMR activates key cellular effectors of the host's innate and adaptive antitumor immunity, culminating in an immunologically coordinated cancer cell death. These findings warrant further work on the potential for MMR to be repurposed as safe and cost-effective cancer immunotherapy to impact cancer patients globally.